THEORIES & PRACTICE. - Kohler, E. L. (The Accounting Review, 1939)
The report of the Committee on Auditing Procedure of the American Institute of Accountants has been revised. The changes have to do with the alteration of the proposed procedures relating to receivables and inventories, whereby physical tests and verification by correspondence have been cut down to practically the same level as called for by previous practice. It might not be unexpected, following the McKesson and Robbins disclosures, that accountants, seeking protection, should amplify their responsibilities in an unnatural degree and reach a somewhat hysterical conclusion from which time alone would have made them recede. The professional criticism was that participating in inventory counts might give the accountant the appearance of appraiser; that tests, fully as acceptable as circularization, are available for determining the existence and propriety of receivables. Except for inserting the reference to a detailed audit, the changes were textual and the same remarks can be applied to the new certificate. The certificate is defective in that it is designed to protect the accountant rather than to give information to those who rely on the information which financial statements are supposed to reveal.